The International Finance Corporation’s Approach to Engaging Clients for Increased Development Impact - Independent Evaluation Group (World Bank, Washington, DC, 2018)
Client engagement is essential for the IFC to support the private sector, maximize finance for development, and contribute to achieving the World Bank Group's twin goals. This IEG evaluation assesses how the IFC has implemented its strategic approach to client engagement since the early 2000s, and its effects on IFC's clients and the development impact of its operations.